Acute pulmonary embolism mimicking COVID-19 pneumonia - Benslima, Najwa (Radiol Case Rep, 2021)
The case of 21-year-old man with an asthma history from childhood presenting severe respiratory distress associated with a right lower thoracic pain has been studied. The non–contrast Computed Tomography (CT)-chest scan showed a basal ground-glass opacity (GGO) of the right lung leading to suspicion of COVID-19 pneumonia. However, the molecular Reverse transcription polymerase chain reaction test and blood serology were negative while laboratory analyses revealed high levels of D-dimers (D-D). In addition, 2 repeated COVID-19 tests were negative. A thoracic CT angiography was disclosed due to the persistence of pain at the lower right thoracic side and hemoptysis that shows a bilateral distal pulmonary embolism with a right-sided basal subsegmental ischemia. We discuss a fortuitous discovery of pulmonary embolism associated with peripheral basal ground-glass opacities similar to radiological manifestations of SARS-CoV-2 pneumonia.